Asian Culture in Positive Politeness: BTS Kim Namjoon on Zach Sang Show YouTube Channel - Jenetha, Fatikha Putri; Firdaus, Dadan; Ruminda, Ruminda (Wanastra: Jurnal Bahasa dan Sastra, 2025)
This study suggests using positive politeness strategies, as seen through the speech of BTS Kim Namjoon. It also seeks to identify Asian cultural habits in communication-based on Namjoon's Asian background. This research also uses a descriptive qualitative approach based on the transcript of the YouTube video. Based on this research, it can be seen that Brown and Levinson's (1987) theory is used as the leading theory of the analysis. The supporting theory of this research comes from Samovar et al. (2013), who suggest the habits of Asians when communicating. This research shows that BTS Kim Namjoon often uses positive politeness in the strategies of "exaggeration" and "include both S and H in the activity."  This research consists of suppositive politeness strategies used by BTS’ Kim Namjoon to uphold the social relationship and maintain the social interactions between the individuals.